Faktor-Faktor yang Meningkatkan Organizational Citizenship Behavior - Niko Sudibjo; Heidi Simanhadi (JRB-Jurnal Riset Bisnis, 2020)
The teacher is the front liner needed to achieve the school's vision and mission because it is the teacher who interacts directly with students and their parents. Teachers who spontaneously contribute more than what is written in the job description are compulsory. So, the impact on overall school effectiveness will be felt and can also reduce tensions between teachers and school management. A teacher's attitude and willingness to go beyond a predetermined target can be translated into the Organizational Citizenship Behavior (OCB) variable of the teacher. This study aimed to determine the effect of perceived organizational support, procedural fairness, and organizational commitment to OCB teachers at SD Methodist Jakarta. The study data were obtained from distributing questionnaires to 28 teachers who were actively teaching in the Methodist Elementary School. This study uses a quantitative approach to the PLS-SEM method, where data analysis uses the SmartPLS v 3.2.7 software to calculate the outer model and the inner model. The results showed that the perception of organizational support, procedural fairness, and organizational commitment had a positive effect on OCB teachers at SD Methodist Jakarta.